Kevin's Predicaments: Power and Celebrity across the Political and Media Fields. (January 2014) - Craig, Geoffrey
This article grounds the concept of political celebrity in the contexts of the differentiated media or journalistic field, and it also investigates the functions of political celebrity in the exercise of political leadership where individuals must negotiate the relationship between the political and media fields. Through a discussion of the changing political fortunes of former Australian Prime Minister Kevin Rudd, the power of political celebrity is attributed to particular structural negotiations between the political and media fields, and also to exploitations of the temporality of political cycles, and the ephemerality of the currency of political celebrity. It is also argued that political celebrity is an unstable phenomenon, partly because it encapsulates a tension between different conceptualizations of subjectivity, where the positing of an autonomous, authentic self competes with a more situational and performative understanding of the self and that this latter understanding of political celebrity is exacerbated in the contexts of post-broadcast democracy.